Differential Dose Distribution in Transition from 3-D CRT to IMRT Treatment Plans for Glioblastoma Multiforme’ at Stage III or IV: A Clinical Study of a Brain Tumor - Malik, Sadiq R; Reza, Shohel; Hossain, MM Shakhawat (Bangladesh Journal of Nuclear Medicine, 2018)
Advancement in Cancer Therapy Technology (CTT) due to Software, Hardware and precise delivery of radiation dose has enhanced the quality of life of cancer patients. This report aims at the application of 3-D CRT (Three Dimensional Conformal Radiation Therapy) and IMRT (Intensity Modulated Radiation Therapy) for a quality of treatment. Other anatomical sites viz. Prostate, Lung, etc. may also be treated provided a better tool is applied for target delineation for which FUSION of CT and MRI images are used to ascertain differences in tissue density. This Fusion image of 3 mm slices offer accurate contouring of the tumor. The oncologist and/or physicist perform delineation of (I) GTV (Gross Tumor Volume), (II) CTV (Clinical Target Volume), (III) PTV (Planning Target Volume), (IV) TV (Treated Volume) and (V) OARs (Organs at Risk). This is done to secure conformal dose distribution and justify the clinical objectives of Tumor Control Probability (TCP) by reducing the normal tissue complication probability (NTCP). The implication of this study outlines the fundamental goal of effective treatment procedures by comparing treatment plans of 3-D CRT and IMRT. Tolerance levels of dose to different organs are optimized by the analysis of random and systemic geometrical deviations, margin on target volumes, conformity index (CI), patient selection process and, of course, the shape and stage of target. The comparative parameters of treatment plans are segmented and tabulated to implicate the application of necessary tools to decide on a treatment plan for similar patients. Bangladesh J. Nuclear Med. 19(1): 64-67, January 2016